Implementasi Komunikasi Internal Perusahaan dalam Menjalankan Flexible Working Arrangements (FWA) - Silvya Nur Septyani; Moch. Armien Syifaa Sutarjo (Journal of Management and Bussines (JOMB), 2022)
Internal communication within a company is an important part to achieve the company's goals, one of which is the successful implementation of Flexible Working Arrangement at PT Telkom Indonesia Tbk where communication technology plays an important role in it. The purpose of this study is to determine the internal communication process that occurs in carrying out Flexible Working Arrangements at PT Telkom Indonesia Tbk. This study uses a qualitative approach with a single case study method to focus on analyzing the actual state of the problem. The results of the study indicate that in the successful implementation of Flexible Working Arrangements, the use of communication technology and the ability of employees to apply their knowledge on this communication technology can streamline the work process during the implementation of the FWA. With the holding of activities and activities as well as providing internal support facilities provided by the company in the form of work support facilities, providing clear information, and the role of superiors in the work process can facilitate the running of FWA in the company environment.. Keywords: Internal Communication, Vertical Communication, Horizontal Communication, Diagonal Communication, Flexible Working Arrangements